Gerakan Pencegahan Stunting Melalui Pemberdayaan Masyarakat di Desa Sumbersekar Dau Malang - Wanda Mawar Dhanik Wanda Mawar Dhanik; Muhammad Irfan Hakim; Maharani Putri Kumalasani; La Vito Valentino Mirrabbirrahim (CV. Multi Kreasi Media, 2022)
Stunting is a serious health problem in Indonesia. Basic Health Research Data (Riskesdas) shows the prevalence of stunting under five in 2018 reached 30.8 percent, which means that one in three toddlers is stunted. Stunting refers to the condition of a child's height being shorter than a child's height in general, due to lack of nutritional intake for a long time in the first 1000 days of life (HPK). When adults, children who are stunted will be vulnerable to attacks of non-communicable diseases such as: heart disease, stroke, diabetes, or kidney failure; hampering Indonesia's demographic bonus where the ratio of the non-working age population to the working age population decreases; threat of reducing intelligence level by 5-11 points. Seeing the dangers of stunting, strategic and systematic steps are needed from various elements of society (stakeholders). Because stunting is one of the causes of community knowledge (especially pregnant women and mothers of children under five) about stunting, this community empowerment program aims to prevent stunting through healthy village design, socialization, training, institutional capacity building, and awareness raising, as well as increasing availability. food. The activity method is cross sectional and community participation, and the research method uses pure description. The population is Posyandu Cadre, Sumbersekar Village Head and his staff, TPPKK Chair and PKK members, and other stakeholders, carried out in August-November 2022. The results of this empowerment activity are increased knowledge, awareness, community capacity in preventing and handling stunting, including in the depth of access to food as a source of nutrition for stunting management.